THE EFFECT OF IRON DEFICIENCY ANEMIA ON ELECTROCARDIOGRAPHIC PARAMETERS IN WOMEN - Umida Sarimsoqova (KLINIK VA FUNDAMENTAL TIBBIYOT TADQIQOTLARI JURNALI, 2026)
Iron deficiency anemia is a widespread metabolic disorder affecting women of reproductive age worldwide. Although primarily regarded as a hematological condition, chronic intracellular iron deficiency causes significant hemodynamic stress and subclinical electrical remodeling of the myocardium. This brief systematic review synthesizes recent high-impact cardiovascular literature to evaluate specific electrocardiographic alterations resulting from tissue hypoxia. The findings consistently demonstrate marked autonomic imbalance in anemic patients, leading to significant heterogeneity of atrial conduction and delayed ventricular repolarization. Parameters such as P-wave dispersion, corrected QT intervals, and transmural dispersion of repolarization were abnormally prolonged compared with healthy control groups. These electrophysiological changes indicate an increased subclinical risk of arrhythmogenesis, particularly atrial fibrillation and ventricular tachyarrhythmias. Integration of clinical studies suggests that these arrhythmogenic substrates are highly reversible following targeted intravenous iron replacement therapy. Recognition of the direct cardiotoxic properties of this pathology is essential for optimizing early diagnostic and therapeutic protocols in the female population.